2008
DOI: 10.1002/cssc.200700144
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidative Desulfurization: A Promising Approach for Sulfur Removal from Fuels

Abstract: Cleaning up their act: Sulfur compounds in fuels can be selectively converted into SO2 by mixing the fuel with a small amount of air at around 300 °C at ambient pressure in a continuous‐flow reactor packed with catalysts such as Pt/CeO2, Cu/CeO2, and CuO/ZnO/Al2O3. The aerobic oxidative desulfurization process opens up a cost‐effective new technology for cleaning fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…1 In view of the importance of desulfurization, several methods for desulfurization of fuels have been reported, such as hydrodesulfurization (HDS), 2,3 extraction, [4][5][6] adsorption, 7-9 oxidation, [10][11][12][13] and bioprocess. 14 HDS process has been used to eliminate sulfur compounds for industry purpose for the past few years; however, this method suffers from severe operating conditions (high temperature, high hydrogen pressure, and capital cost) and it is less effective for removing refractory sulfur compounds, such as benzothiophene (BT), dibenzothiophene (DBT), and their alky derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…1 In view of the importance of desulfurization, several methods for desulfurization of fuels have been reported, such as hydrodesulfurization (HDS), 2,3 extraction, [4][5][6] adsorption, 7-9 oxidation, [10][11][12][13] and bioprocess. 14 HDS process has been used to eliminate sulfur compounds for industry purpose for the past few years; however, this method suffers from severe operating conditions (high temperature, high hydrogen pressure, and capital cost) and it is less effective for removing refractory sulfur compounds, such as benzothiophene (BT), dibenzothiophene (DBT), and their alky derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, extractive desulfurization (EDS) [9,10], adsorptive desulfurization (ADS) [11,12], oxidative desulfurization (ODS) [13][14][15][16][17][18] and biological desulfurization (BDS) [19,20]. Among all the processes, ODS is a promising process with high desulfurization efficiency under mild reaction conditions [21][22][23][24]. The most popular oxidant used in the ODS system is hydrogen peroxide (H 2 O 2 ) for its high oxidation efficiency and water is the only oxidative product after reaction [25][26][27].…”
mentioning
confidence: 99%
“…In the scientific literature, the vapor phase oxidative desulfurization of motor fuels is represented by few works, in particular, by works of Yong Lu et al on aero bic desulfurization of fuels in the presence of Cu/CeO 2 , Pt/CeO 2 , and CuZnAl catalysts [4,5]. These papers demonstrated that, in the presence of these catalysts, sulfur as a part of sulfur containing organic molecules can be oxidized selectively to SO 2 by the introduction of small amounts of oxygen into the fuel at 300°C under atmospheric pressure.…”
mentioning
confidence: 99%
“…These papers demonstrated that, in the presence of these catalysts, sulfur as a part of sulfur containing organic molecules can be oxidized selectively to SO 2 by the introduction of small amounts of oxygen into the fuel at 300°C under atmospheric pressure. The CuO/ZnO/Al 2 O 3 catalyst exhibited the highest activity in the oxidative desulfur ization of diesel fuels, providing 79% efficiency [5]. It was assumed [4,5] that this is due to the high activity of Pt/CeO 2 and Cu/CeO 2 in olefin oxidation, which results in a decrease in the amount of oxygen spent on the oxidation of organosulfur molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation